Association of serum Matrix Metalloproteinase 1, 2 and 3 with Oral Squamous Cell Carcinomas - Sana Sarmad, Saher Sarmad, Muhammad Adnan Sadiq, Maira Mehmood Bokhari, Shama Akram, Sumera Saghir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Squamous cell carcinoma involving the oral cavity (OSCC) is a malignant lesion prone to local dissemination and distant metastasis. It causes severe morbidity in the afflicted patients and has low 5-year survival rate. The current study explored the serum levels of extracellular matrix degrading enzymes, the MMPs 1,2 and 3 in OSCC patients and normal healthy controls. Materials and methods: Blood samples from thirty eight patients suffering from OSCC and thirty eight normal healthy controls were included in the study. The MMP 1 - 3 were estimated by multiplex ELISA. Results: Out of three MMPs analyzed between cases (n=38) and controls (n=38), significant differences were observed in serum MMP levels in MMP 1 and 2. In MMP 1, cases were recorded to have higher values, as evidenced by mean and median levels. ROC curve analysis, used to assess the prognostic and diagnostic worth of the two statistically significant markers (MMP 1, 2) indicated that both markers had area under the curve (AUC) significantly better than 0.5. For MMP 2, control group had higher serum levels than cases. Conclusions: MMP 1 expression was found significantly elevated in cases with 71.0% sensitivity and 56.3 specificity so it can be further evaluated as a drug target as well as diagnostic and prognostic tumor marker. Keywords: Oral squamous cell carcinoma, Matrix metalloproteinase.